2013
DOI: 10.1124/jpet.113.208520
|View full text |Cite
|
Sign up to set email alerts
|

Rolipram Improves Renal Perfusion and Function during Sepsis in the Mouse

Abstract: Microcirculatory dysfunction is correlated with increased mortality among septic patients and is believed to be a major contributor to the development of acute kidney injury (AKI). Rolipram, a selective phosphodiesterase 4 (PDE4) inhibitor, has been shown to reduce microvascular permeability and in the kidney, increase renal blood flow (RBF). This led us to investigate its potential to improve the renal microcirculation and preserve renal function during sepsis using a murine cecal ligation and puncture (CLP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 54 publications
2
58
0
1
Order By: Relevance
“…Given the complex and rapid development of sepsis-induced AKI in this model (55), it is not surprising that delayed therapy with Mito-TEMPO did not completely restore GFR. Targeting renal vascular resistance (22) or oxidative stress (23,55) with delayed therapy also only partially restored GFR. These findings support the view that combination therapy will likely be the most efficacious in the septic patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the complex and rapid development of sepsis-induced AKI in this model (55), it is not surprising that delayed therapy with Mito-TEMPO did not completely restore GFR. Targeting renal vascular resistance (22) or oxidative stress (23,55) with delayed therapy also only partially restored GFR. These findings support the view that combination therapy will likely be the most efficacious in the septic patient.…”
Section: Discussionmentioning
confidence: 99%
“…Biotelemetry was used to measure mean arterial pressure (MAP) and heart rate (HR) in conscious mice as described previously (22). Under isoflurane anesthesia, telemetry transmitters (Data Sciences International, St. Paul, MN) were implanted into the carotid artery of mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI occurs in nearly half of all septic patients and is associated with increased mortality. [25] It has been suggested that AKI in sepsis is correlated with important destructive effects. While detection of acute lung injury is not easy in early stages, the authors suggested that it can indicate severity of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Intravital video microscopy (IVVM) was performed as described previously elsewhere Holthoff et al, 2013). Briefly, after anesthesia with isoflurane, fluorescein isothiocyanate-labeled dextran (2 mmol/kg in 3 ml/kg normal saline) was administered via the penile vein to visualize the capillary vascular space.…”
Section: Methodsmentioning
confidence: 99%